2013
DOI: 10.1093/cid/cit122
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial: Comparative Effectiveness of Cephalexin Plus Trimethoprim-Sulfamethoxazole Versus Cephalexin Alone for Treatment of Uncomplicated Cellulitis: A Randomized Controlled Trial

Abstract: NCT00676130.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 27 publications
2
82
1
2
Order By: Relevance
“…It is possible that S. aureus is not the causative agent in most cases of cellulitis where it was isolated but rather adopts an opportunistic bystander role. This is supported by studies that demonstrate no extra benefit when adding an antibiotic active against MRSA in the presence of detectable MRSA (Pallin et al, 2013). The extensive tissue damage caused by streptococcal toxins may produce an environment that promotes S. aureus multiplicationthis is supported by the detection of both organisms in five of the patients in our study.…”
Section: Discussionsupporting
confidence: 80%
“…It is possible that S. aureus is not the causative agent in most cases of cellulitis where it was isolated but rather adopts an opportunistic bystander role. This is supported by studies that demonstrate no extra benefit when adding an antibiotic active against MRSA in the presence of detectable MRSA (Pallin et al, 2013). The extensive tissue damage caused by streptococcal toxins may produce an environment that promotes S. aureus multiplicationthis is supported by the detection of both organisms in five of the patients in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Since more than 90% of community-acquired (CA-MRSA) and hospital acquired (HA-MRSA) strains are still susceptible to trimethoprim-sulfamethoxazole (TMP-SMX, or SXT) (2)(3)(4)(5), new attention has been drawn to this old drug. For example, two recent randomized placebo-controlled studies evaluated the effect of SXT in skin abscesses after incision and drainage in children and adults mostly caused by CA-MRSA (6)(7)(8). Furthermore, De Angelis et al suggested the use of SXT and clindamycin as first-line drugs as a therapeutic option in patients suffering from CA-MRSA infections (9).…”
mentioning
confidence: 99%
“…A recent trial involving 146 patients with uncomplicated cellulitis who were treated with TMP-SMX plus cephalexin or cephalexin alone showed no significant difference in clinical cure rates after 12 days (85% and 82%, respectively; difference, 3 percentage points; 95% confidence interval, −9.3 to 15; P = 0.66). 41 However, the trial was relatively small -powered to detect only a 13% difference in cure rates -and the 95% confidence interval for the difference in these rates could not rule out the superiority of the former regimen. This same comparison of antibiotics for cellulitis is being investigated in one of the large NIH-sponsored studies mentioned above (NCT00729937), which involves approximately 500 participants.…”
Section: Antibiotic Treatmentmentioning
confidence: 97%